2005
DOI: 10.1007/s10038-005-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at codons 56 and 174 of the prion-like protein gene (PRND) are not associated with sporadic Creutzfeldt-Jakob disease

Abstract: Association between sporadic Creutzfeldt-Jakob disease (CJD) and the prion-like protein gene (PRND) has been reported in the German population. To investigate whether the PRND polymorphisms are associated with an increased risk for developing sporadic CJD in the Korean population, we compared the genotype and allele frequencies of PRND polymorphisms in 110 sporadic CJD patients with those in 102 healthy Koreans. Two polymorphisms (P56L, T174 M) in Koreans were found in the open reading frame (ORF) of PRND. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In our previous studies, we found that in the Korean population, codons 129 and 219 polymorphisms within the ORF of PRNP and polymorphism at 3 untranslated region +28 of PRND are associated with sporadic CJD [34][35][36] . However, PRNP 1368 polymorphism and codons 56 and 174 polymorphisms of PRND did not correlate with the development of sporadic CJD [37,38] .…”
Section: Discussionmentioning
confidence: 97%
“…In our previous studies, we found that in the Korean population, codons 129 and 219 polymorphisms within the ORF of PRNP and polymorphism at 3 untranslated region +28 of PRND are associated with sporadic CJD [34][35][36] . However, PRNP 1368 polymorphism and codons 56 and 174 polymorphisms of PRND did not correlate with the development of sporadic CJD [37,38] .…”
Section: Discussionmentioning
confidence: 97%
“…Studies on a correlation between the PRND polymorphisms and neurodegenerative diseases in various populations have shown contradictory results [38][39][40][41] . In the future, to evaluate the possible involvement of PRND in VaD, we will investigate the relationship between the PRND polymorphisms and VaD in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…However, CTSD C224T, PRNP 1368 polymorphism and polymorphisms in codons 56 and 174 of PRND did not affect the susceptibility to sporadic CJD [39,40,41]. …”
Section: Discussionmentioning
confidence: 99%